Legal culture of a civil society (Journal of actual problems of jurisprudence, 2019)
This article is devoted to analysis of civil society legal culture. The purpose of the article is to highlight valuablereference points of legal culture of the Republic of Kazakhstan in the process of democratic state development. Inarticle various approaches to understanding of legal culture from positions of the socially-philosophical analysis areoffered. Scientific work is written on the basis of scientific researches of the Kazakhstan and foreign authors concerningthe nature of the right, legal culture, its valuable reference points in the course of formation of a civil society and alawful state in Republic Kazakhstan.Key words: legal culture, democratic state and its values, civil society, nature of legal reforms of Kazakhstan, absolutevalues of the human personality.